1995
DOI: 10.1101/gr.5.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a mutation in the H5 domain of Girk2 as a candidate for the weaver mutation.

Abstract: A mutation in the GIRK2 inwardly rectifying K ÷ channel was mapped recently to the region of mouse chromosome 16 containing the wv gene and shown to occur in mutant but not in wild-type mice. We demonstrate tight linkage of the Girk2 mutation to the wv phenotype and refine the localization of the weaver (wv) gene on recombinational and physical maps. This linkage between Girk2 and ~ has existed since at least 1988 in descendants of the original mutation maintained in CS7BLI6 animals. Giric2. is shown to be tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…For example, defects in granule cell migration and Bergmann glial fibers leading to loss of granule cells characterize the homozygous weaver mutant mouse [Rakic et al, 1973a,b;Smeyne and Goldowitz, 1989]. A candidate gene, Girk2, homologous to a human gene localized to the long arm of chromosome 21, was proposed as the causative gene in the weaver mouse [Mjaatvedt et al, 1995;Bandmann et al, 1996]. Loss of dopaminecontaining neurons in the substantia nigra and other nuclei was also observed in weaver mutant mice, suggesting a more widespread neuronal defect [Graybiel et al, 1990], although no definite evidence of cell loss in the substantia nigra was observed in this case.…”
Section: Discussionmentioning
confidence: 99%
“…For example, defects in granule cell migration and Bergmann glial fibers leading to loss of granule cells characterize the homozygous weaver mutant mouse [Rakic et al, 1973a,b;Smeyne and Goldowitz, 1989]. A candidate gene, Girk2, homologous to a human gene localized to the long arm of chromosome 21, was proposed as the causative gene in the weaver mouse [Mjaatvedt et al, 1995;Bandmann et al, 1996]. Loss of dopaminecontaining neurons in the substantia nigra and other nuclei was also observed in weaver mutant mice, suggesting a more widespread neuronal defect [Graybiel et al, 1990], although no definite evidence of cell loss in the substantia nigra was observed in this case.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have been confronted by findings that the GIRK2 channel is not functional in the cultured weaver neurons (Mjaatvedt et al, 1995;Surmeier et al, 1996). Our earlier results indicate that neurite outgrowth of the weaver granule neurons can be restored by drugs that reduce proteolysis and accumulation of neurotoxic peptides derived from the B2 chain of laminin along the neuronal cell surfaces (Murtomäki et al, 1995;Liesi and Wright, 1996).…”
Section: Introductionmentioning
confidence: 90%
“…There is, of course, ample precedent for the idea that ion channels mutated in the permeation pathway display more stable open states, presumably because the permeation pathway is also in contact with the regions of the channel thought to govern gating (Revah et al 1991, De Biasi et al 1993, Labarca et al 1995, but the argument is less direct than for the permeation pathway. Furthermore, several reports showed no constitutive activation of the wvGIRK2 channel-and no GIRK currents at all-in weaver mice (Mjaatvedt et al 1995, Surmeier et al 1996, Lauritzen et al 1997, and constitutive activation was incomplete when only low levels of wvGIRK2 were expressed in oocytes (Slesinger et al 1996). Also, wvGIRK2 channels were insensitive to G protein subunits in excised inside-out patches from CHO cells (Navarro et al 1996).…”
Section: ‫ם2‬mentioning
confidence: 99%